Hip Dysplasia in Dogs: Control and Prevention - Rodrigues, D. (2013)
Hip dysplasia (HD) is an orthopaedic pathology with high prevalence in dogs, especially in large and giant breeds. It has a polygenic origin and is influenced by several factors such as age, sex, nutrition, metabolism, physical activity and hormones. Animals affected with this disease are born with normal joints but as they develop, joint changes appear. These changes may be expressed by lameness, gait abnormalities, hip instability and pain in full extension of the joint. To reduce the HD prevalence, selective breeding programmes have been implemented in which only animals free of disease or with minimal articular changes can reproduce. As these programmes do not always have the desired success, early radiographs should be performed in susceptible animals, in order to slow the progression of changes. The aim of this review is to summarize canine HD control and prevention aspects, with reference to the factors that predispose to disease, and the various treatment options. The role played by the veterinary nurse in advising the HD dog owners on disease management and also on how to avoid the risk factors in order to reduce the number of affected animals, is also discussed